Synergism among lactic acid, sulfite, pH and ethanol in alcoholic fermentation of Saccharomyces cerevisiae (PE-2 and M-26) - Dorta, C.; Oliva-Neto, P.; de-Abreu-Neto, M. S.; Nicolau-Junior, N.; Nagashima, A. I. (Springer, 2006)
The industrial production of ethanol is affected mainly by contamination by lactic acid bacteria besides others factors that act synergistically like increased sulfite content, extremely low pH, high acidity, high alcoholic content, high temperature and osmotic pressure. In this research two strains of Saccharomyces cerevisiae PE-2 and M-26 were tested regarding the alcoholic fermentation potential in highly stressed conditions. These strains were subjected to values up to 200 mg NaHSO3 l(-1), 6 g lactic acid l(-1), 9.5% (w/v) ethanol and pH 3.6 during fermentative processes. The low pH (3.6) was the major stressing factor on yeasts during the fermentation. The M-26 strain produced higher acidity than the other, with higher production of succinic acid, an important inhibitor of lactic bacteria. Both strains of yeasts showed similar performance during the fermentation, with no significant difference in cell viability.
Keywords: ethanol; fermentative stress; lactic acid; low pH; Saccharomyces cerevisiae; sulfite